Proceedings of the 11th Joint Conference on Computer Vision, Imaging and Computer Graphics Theory and Applications 2016
DOI: 10.5220/0005716801500158
|View full text |Cite
|
Sign up to set email alerts
|

Robust Facial Landmark Detection and Face Tracking in Thermal Infrared Images using Active Appearance Models

Abstract: Long wave infrared (LWIR) imaging is an imaging modality currently gaining increasing attention. Facial images acquired with LWIR sensors can be used for illumination invariant person recognition and the contactless extraction of vital signs such as respiratory rate. In order to work properly, these applications require a precise detection of faces and regions of interest such as eyes or nose. Most current facial landmark detectors in the LWIR spectrum localize single salient facial regions by thresholding. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 14 publications
0
28
0
Order By: Relevance
“…With up to 10 fps, this method meets the runtime requirements for many real-time applications. Howevwer, the fitting performance needs to be analyzed critically since the authors of [17] have shown that these values usually result in poor fitting performance in infrared data.A deep alignment network trained by following the results given in [7]. With the trained algorithm, we implemented two different frame update strategies: an instance that is updated with the bounding box of the detected face (bounds-DAN) and a version that uses the detected landmark points directly for the shape update (shape-DAN).A ShapeNet following [18].…”
Section: Experiments and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With up to 10 fps, this method meets the runtime requirements for many real-time applications. Howevwer, the fitting performance needs to be analyzed critically since the authors of [17] have shown that these values usually result in poor fitting performance in infrared data.A deep alignment network trained by following the results given in [7]. With the trained algorithm, we implemented two different frame update strategies: an instance that is updated with the bounding box of the detected face (bounds-DAN) and a version that uses the detected landmark points directly for the shape update (shape-DAN).A ShapeNet following [18].…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Using the bounding box returned by the face detector and the model’s mean shape as initialization, we optimize the model parameters until optimal landmark positions are found. As shown in [17], feature-based AAMs allow precise landmark localization in thermal facial images. While yielding a high grade of precision, their main downside is the long fitting time as AAMs rely on multivariate optimization.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The automation of the measurement process may improve its use cases. In particular, recent advanced thermal ROI tracking algorithms could help this [9,[28][29][30]. However, this means that a thermal camera needs to be placed in front of the person during at least these measurements interfering with the activity and predicting the stress may indeed occur in that period of time.…”
Section: Introductionmentioning
confidence: 99%
“…However, these benchmark methods failed to detect landmarks correctly when applied to the IR images (Figure 3a and 3b). Previous work on infrared based facial analysis and ROI tracking primarily explored the use of standard machine learning techniques (Wesley, Buddharaju et al 2012, Ghiass, Arandjelović et al 2014, Kopaczka, Acar et al 2016, Kopaczka, Nestler et al 2017. These models allow optimal landmark detection in some cases but need further improvement as they rely on data attributes (features) which in the case of IR facial images lack the details present in visible spectrum images.…”
Section: Facial Landmark Estimationmentioning
confidence: 99%